2017
DOI: 10.4081/aiol.2017.7207
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity ecosystem functioning research in freshwater phytoplankton: A comprehensive review of trait-based studies

Abstract: In an effort to reach a clearer mechanistic understanding of the influence of biological diversity on ecosystem functioning, research in the field is increasingly applying a trait-based approach. In this comprehensive review, I searched for and analyzed studies that focused on the relationship between biodiversity and ecosystem functioning (BEF) using a trait-based approach in freshwater phytoplankton from lentic systems (lakes, ponds, reservoirs). I found that this type of studies is very rare and included a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Mouquet et al, 2002; Seibold et al, 2018). Such complexity in the BEF relationship has been attributed to a rich array of factors, including disparate definitions of diversity and functions (Hooper et al, 2005), spatial heterogeneity (Griffin et al, 2009), environmental context (Hong et al, 2022; Ratcliffe et al, 2017), species traits (Strong et al, 2015; Venail, 2017) and trophic structure (Wang & Brose, 2018). For example, experimental studies have demonstrated that the presence of herbivores can largely alter the positive relationship between grassland species diversity and plant biomass by altering plant species composition via top‐down control (Mulder et al, 1999; Seabloom et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Mouquet et al, 2002; Seibold et al, 2018). Such complexity in the BEF relationship has been attributed to a rich array of factors, including disparate definitions of diversity and functions (Hooper et al, 2005), spatial heterogeneity (Griffin et al, 2009), environmental context (Hong et al, 2022; Ratcliffe et al, 2017), species traits (Strong et al, 2015; Venail, 2017) and trophic structure (Wang & Brose, 2018). For example, experimental studies have demonstrated that the presence of herbivores can largely alter the positive relationship between grassland species diversity and plant biomass by altering plant species composition via top‐down control (Mulder et al, 1999; Seabloom et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The use of FD components in the context of BEF in phytoplankton has only started very recently (Abonyi et al, 2018a, b;Ye et al, 2019). Trait-based functional diversity measures in BEF have recently been reviewed by Venail (2017).…”
Section: The Functional Diversity-ecosystem Functioning Relationship mentioning
confidence: 99%
“…The wellknown paradox of Hutchinson asking how so many species may coexist in phytoplankton (Hutchinson, 1961) has been reversed to how many species ensure ecosystem functioning (Ptacnik et al, 2010b). Based on functional traits, however, almost half of the studies reported null or negative relationship between functional diversity and ecosystem functioning (Venail, 2017). Recently, Abonyi et al (2018a, b) argued that functional diversity based on trait categories (i.e., functional trait richness-FTR) and Reynolds' ecological groups (i.e., functional group richness-FGR) represented different aspects of community organisation in phytoplankton.…”
Section: The Functional Diversity-ecosystem Functioning Relationshipmentioning
confidence: 99%